Absorption enhancement in 1D Ag/SiO2 metallic-dielectric photonic crystals - Chen, Su; Wang, Yang; Yao, Duanzheng; Song, Zhitang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The one-dimensional Ag/SiO2 metallic-dielectric photonic crystals (PCs) have been prepared. The absorption enhancement effect over the corresponding metal of 1D Ag/SiO2 metallic-dielectric multi-layer structures has been measured. The enhancement effect increases with the number of layers increasing. The origin of this phenomenon and its effect on the transmittance and reflectance have been discussed.
Optica Applicata, Vol. 39, 2009, nr 3, s. 473-479
Keywords: optyka; photonic crystal; metallic-dielectric; absorption enhancement